THE CULTURE OF SPEECH AND TEACHER COMPETENCY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The future of each nation and state is connected with the level of upbringing and education of the younger generation. The role of the teacher is invaluable. According to Academician D. Likhachev, “Teaching is an art, work is no less creative than the work of a writer or composer, but harder and more responsible, he not only teaches, but also educates personality, knowledge and love, attitude to business ".